Ibadat Ekumene dan Dampaknya Terhadap Integritas Iman Kristen - Dian Labo Mengkala; Hendrikus Rinaldi Amsikan (Perspektif, 2026)
This study aims to examine ecumenical worship and its impact on the integrity of the Christian faith within the context of increasingly plural ecclesial life. Ecumenical worship is understood as a form of interdenominational liturgical encounter that expresses the call to Christian unity, as encouraged by various official Church documents. However, this spirit of unity is accompanied by a firm insistence that participation in the ecumenical movement must not lead to doctrinal compromise or the relativization of the teachings of the faith. This research employs a library research method by examining official Church documents, theological works, and relevant academic literature. In particular, the analysis focuses on Church teachings that promote involvement in the ecumenical movement, such as the document Unitatis Redintegratio, while also providing theological boundaries to safeguard the purity of the faith. The approach used includes theological, historical, and critical-reflective analysis in order to identify the balance between the demand for unity and fidelity to the teachings of the faith. The findings of this study indicate that ecumenical worship, as supported by official Church teachings, has a positive impact in strengthening awareness of the unity of the Body of Christ, fostering mutual respect among denominations, and enriching the faith understanding of believers. Nevertheless, the Church also clearly warns of potential dangers, such as doctrinal compromise and the relativization of the truth of the faith, if ecumenical practices are not carried out with theological prudence. Thus, the integrity of the Christian faith is understood as fidelity to the core teachings of the faith, which goes hand in hand with openness to ecumenical dialogue. This study affirms that ecumenical worship can make a positive contribution to the life of the Church when it is carried out in accordance with official Church guidelines, balancing the spirit of unity with a commitment to the authenticity of the faith.